The Influence of Perceived Ease of Use and Usefulness of The Academic Registration System on the Attitude of Using online Study Plan Card (KRS) - Tri Rahmat (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2019)
This research investigated the factors affecting the academic registration system used by students in STIE Panca Bhakti Palu based on the Theory of Technology Acceptance Model (TAM). Research data were collected through the survey. Out of 294 questionnaires distributed to the respondents, 269 questionnaires were returned back (92%), while 25 questionnaires (8%) were incompletely filled in. The obtained data underwent the Structural Equation Model (SEM) analysis using Amos 20 for Windows software. The results of this research showed that the ease of use and usefulness had a positive and significant influence on users’ attitude in using the system. Meanwhile, the ease of use positively and significantly influenced the usefulness of the system.